Development of Molecular Markers Associated with Resistance to Gray Mold Disease in Onion (Allium cepa L.) through RAPD-PCR and Transcriptome Analysis - So-Jeong Kim (MDPI AG, 2021)
Onions (Allium cepa L.) are one of the most consumed vegetable crops worldwide and are damaged by several fungal diseases in the field or during storage. Gray mold disease caused by the necrotrophic pathogens Botrytis cinerea and Botrytis squamosa is a disease that reduces the productivity and storage life in onions. However, it is difficult to control gray mold disease in onions by using physical and chemical methods. Breeding resistant onions against gray mold disease can reduce the damage caused by pathogens, reduce the labor required for control, and reduce environmental pollution caused by fungicides. However, onions have a large genome size (16Gb), making them difficult to analyze, and have a biennial cycle, resulting in a very long breeding period. Therefore, in this study, markers were developed to shorten the onion breeding period. First, random amplified polymorphic DNA (RAPD) was performed to confirm the genetic relationship between the gray mold disease-resistant and -susceptible lines through a dendrogram. In addition, the sequence characterized amplified region (SCAR)-OPAN1 marker to select resistant lines was developed using a polymorphic RAPD fragment. Second, the RNA-seq of the gray mold-resistant and -susceptible onion lines were analyzed using NGS technology. Using the RNA-seq results and DEG and GO analyses were performed, and the variants, such as SNPs and indels, were analyzed to develop a selectable marker for the resistant line. This study developed the SNP-3 HRM marker for selecting gray mold disease-resistant lines by using the SNPs present in the aldo-keto reductase (AKR) gene with high expression levels in these lines. The SCAR-OPAN1 and SNP-3 HRM markers developed in this study could be used to select gray mold disease-resistant onions in breeding programs to reduce the damage caused by gray mold disease.